Evaluation of 3-dimensional rotational venography for the diagnosis of non-thrombotic iliac venous lesion - Xu, Yingjiang; Wu, Jian; Cheng, Yongjia; Chen, Gang; Han, Xinqiang; Sheng, Yuguo; Wu, Xuejun; Wang, Wenming (Frontiers in Cardiovascular Medicine, 2023)
Background: The purpose of this study was to determine the technical feasibility and safety of 3D rotational venography (3D-RV) in the diagnosis of non-thrombotic iliac vein lesions compared with traditional 2D-digital subtraction angiography (2-DSA). Methods: The general epidemiological data (including age, gender), clinical manifestations (including major symptom, affected extremity, CEAP classification, comorbidity, stenosis rate), and intra-operative findings (iliac vein indentation position, collateral circulation, procedure time, X-rays dose, contrast agent dosage) of 61 NIVL patients who were assessed by 3D-RV and traditional 2-DSA between October 2018 to October 2022 were obtained and analyzed. Results: A total of 61 consecutive patients with symptomatic NIVL from our institution were enrolled in this study. With the aggravation of iliac vein stenosis, the proportion of indicators such as contralateral formation and iliac vein compression indentation reflecting the severity of compression under 3D-RV reconstruction increased significantly. Also, significant differences were observed between the 3D-RV and 2-DSA groups concerning procedure time (10.56±0.09 s vs. 12.59±0.37 s; p＜0.01), X-ray dose (41.25±0.21 mGy vs. 81.59±1.69 mGy; p＜0.01) and contrast agent dosage (21.48±0.24 mL vs. 33.69±0.72 mL; p＜0.01). Contralateral iliac vein imaging (p=0.002), pelvic collateral vein imaging (p=0.03), and external iliac vein indentation (p=0.001) were found to influence the severity of iliac vein compression. Conclusion: 3D-RV can display dynamic stereo image information of NIVL, augmenting the information obtained from traditional 2-DSA. Contralateral iliac vein imaging, pelvic collateral vein imaging, and external iliac vein indentation can be used to evaluate the severity of iliac vein compression to some extent.